Biochemical events related to glial response in spinal cord injury (2018)
Introduction: Spinal cord injury (SCI) is a devastating event with physical, psychological and socioeconomic implications. Morphophysiological changes are observed in the tissue close to the injury, which allow determining the functional recovery of the medullary segment and the effector organs that depend on the injured axonal tracts.Objective: To describe the most relevant sequential biochemical events of glial cells response after SCI.Materials and methods: A search of scientific publications released in the past 18 years was carried out in PubMed and Science Direct databases, with the terms spinal cord injury (SCI), SCI pathophysiology, SCI inflammation, microglia in SCI, glial scar and chondroitin sulfate proteoglycans (CSPG).Results: The pathophysiological processes resulting from SCI are determinant for the neurological recovery of patients. Activation of glial cells plays an important role in promoting bioactive molecules and the formation of physical barriers that inhibit neural regeneration.Conclusion: Knowledge of neurobiological changes after SCI allows a greater understanding of the pathophysiology and favors the search for new therapeutic alternatives that limit the progression of the primary injury and minimize secondary damage, responsible for neurological dysfunction.